POTENSI PAJAK AIR TANAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN MAROS - Andi Jam'an; Rustan; Siti Fatimah Maulana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
This study aims to measure the potential level of groundwater tax on local revenue in Maros district. This type of research is a qualitative descriptive method. The data collection technique used is by looking for records sourced from documents that already exist in the relevant agencies, namely the Regional Revenue and Finance Management Agency of Maros Regency. The data processed by the author is report data which has become documentation of the realization of revenue in Maros Regency for the 2015-2018 period. The focus of research is on the potential and growth rate of the Maros district groundwater tax. The research location is at the Regional Finance and Revenue Management Agency of Maros Regency. The results of this study indicate that extracting the potential for groundwater tax in Maros Regency produces a very good percentage and continues to increase because the amount of realized groundwater tax exceeds the potential amount. The BPKPD of Maros Regency as a tax manager takes full advantage of the potential of the groundwater tax. However, evaluation is always needed in order to maintain the utilization of its potential and also be careful considering that the difference between the total amount of potential and its realization is still very small.